Selected integrated farming system models for enhanced income - Srivastava, A. P. (Indian Farming, 2018)
The interventions in Integrated Farming System mode covering croplivestock- aquaculture were planned and demonstrated, considering the overall need of the area, available technological options, market accessibility both for input and produce etc. These resulted in increased percolation; reduced evaporation due to subsurface storage; low risk of breaching/ damage in heavy rain; the natural drainage line is not disturbed and further development of washes, gullies stopped due to controlled runoff movement; low-cost as compared to check dam and simple technology easily understood by farmers.